Effectiveness of Anticoagulants in Reducing D-Dimer Levels in COVID-19 Patients: A Retrospective Study - Winduhani Astuti, Lelly; Fajriah, Shofiatul; Rilawati, Fentyana; Istiqomah, Nurul (Jurusan Farmasi Universitas Negeri Gorontalo, 2025)
Coronavirus Disease 2019 (COVID-19) is an acute respiratory infection caused by the SARS-CoV-2 virus. SARS-CoV-2 infection is often associated with blood clotting disorders, both at the microvascular and macrovascular levels due to hypercoagulability. Changes in blood clotting status are indicated by high levels of D-dimer and fibrinogen. The study aimed to evaluate the effectiveness of three anticoagulant therapies in reducing D-dimer levels in COVID-19 patients. The research employed an observational analytical method with a retrospective cross-sectional study design. The results showed significant differences in D-dimer reduction among the treatment groups. The mean reductions in D-dimer levels for patients receiving anticoagulant therapy with heparin, enoxaparin, and fondaparinux were 1.397 µg/L, 2.607 µg/L, and 2.855 µg/L, respectively. Statistical analysis indicated a significant difference among the groups (P 0.05). It can be concluded that fondaparinux demonstrated a greater reduction in D-dimer levels compared to heparin and enoxaparin.